Reference Evapotranspiration Mapping of Libya - Ikhneifir, Ali Alagab; Bubareek, Hafid M. Y.; Balomi, Fouad M. H (Al-Mukhtar Journal of Sciences, 2023)
Estimation of evapotranspiration plays a essential role in water resource management. Therefore, understanding the spatial and temporal variation pattern of reference evapotranspiration (ETO) is crucial for the proper management of water resources and prioritization of their use. This study was conducted to obtain maps showing the reference evapotranspiration values for the area confined between latitudes 19.45o and 33.16o north, and longitudes 9.4o and 25.15o east, which includes the entire area of Libya. Reference Evapotranspiration values were estimated using the Omar Al-Mukhtar University Omu-ET model.1.0.0 based on climate data for the period from 1990 to 2020, represented by (temperature, relative humidity, wind speed, and short-wave solar radiation), which were extracted from the NASA website (The Power Project) for the selected 288 locations. To produce the best digital map of ETO values ​​and climate data, The spatial interpolation methods (IDW, Kriging, Spline) in Geographic Information Systems (GIS) software were compared using spatial statistical interpolation techniques (Mean Error ME and Square Root Mean Error RMSE), and the Spline method was adopted as the best method for interpolation mapping as it gave the smallest RMSE value and the lowest ME value if compared to the results of IDW and Kriging. The ETO results obtained from Omu-ET model.1.0.0 were used to prepare a computer model in Arabic and English using Microsoft Excel and the Visual Basic for Applications programming language, which was named ETO Libya. ETO Libya Provides ETO values monthly and annually for any point located within the area of Libya which requires only the location coordinates.